Determinants and Impacts of Initial Day Return of REIT IPOs: Evidence from U.S. REITs Market - Zhang, Tian (2015)
This study examines the initial day return of REIT IPOs using a sample of 174 U.S. Real Estate Investment Trust (REIT) IPOs during the period 1995 to 2014 and finds a significant 2.69% underpricing. The study employs OLS regression analysis to investigate the determinants of initial day return of U.S. REIT IPOs. Offering size and UPREIT are statistically significant and positively related to initial day return. On the other hand, offering price, mortgage REITs and New York Stock Exchange show statistically significant negative relationship with initial day return. In addition, the study reports that initial day return is closely related to return for 1 month after IPO and return for 6 months after IPO at the 1% significance level. The impact of market condition on REITs’ performance after IPO is not observed.